Pozyskiwanie informacji publicznej przez dziennikarza - Jabłoński, Mariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The main purpose of this elaboration is to present the analyses of rules, the procedure mode of realization of the right of access to public information by journalists. The author focuses on presenting the meaning of notions: the press, the journalist, as well as the relation between the procedure of sharing and spreading the information defi ned in regulations: the press law and the law on access to public information.
Keywords: informacja publiczna; dziennikarze